Detecting single events in large shell mounds: A GIS approach to Cabeço da Amoreira, Muge, Central Portugal. (April 2018) - Gonçalves, Célia; Cascalheira, João; Costa, Cláudia; Bárbara, Sofia; Matias, Roxane; Bicho, Nuno
Abstract: During the 2014 archaeological campaign in the Mesolithic shell midden of Cabeço da Amoreira (Muge, Central Portugal) a concentration over a small area, approximately 1 m 2, of faunal remains with a single taxon (red deer), lithics, charcoal and fire-cracked rocks was identified in one of the shell-rich layers of the mound. Here we present the results of the analysis of bone and lithic materials coming from that feature, as well as refitting data from both classes and correspondent GIS-based spatial analysis, using Kernel Density Estimation and Ripley's K function. All these procedures allowed the identification of non-random density patterns, the definition of clear spatial limits for the feature, and to attest the unique character of the context as a single depositional event within the Cabeço da Amoreira shell mound. Alternative hypothesis for the natural and cultural processes involved in the formation of the feature are suggested, including the possibility that it corresponds to a refuse disposal of a short episode of carcass processing but also that some social-based purposes might have been involved. Highlights: GIS analysis for the study of shell mound anthropogenic features Spatial definition of single deposition events in shell mounds Differential shell midden formation processes and spatial organization